On the some connections of fibre spaces - Bliznikas, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Близникас. О некоторых связностях расслоенных пространствV. Bliznikas. Apie kai kuriuos išsluoksniuotų erdvių sąryšius